(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the transformation of the heroic ideal in English literature, tracing its evolution from the collective, warrior-centered model of the Anglo-Saxon period to the introspective and individualistic hero of the Romantic era. By examining key literary texts such as Beowulf and selected works of Romantic poets, the study highlights how social values, religious beliefs, and historical changes reshaped the concept of heroism. The Anglo-Saxon hero is defined by physical strength, loyalty, and communal responsibility, whereas the Romantic hero emphasizes personal emotion, imagination, and individual freedom. The article argues that this shift reflects a broader cultural transition from external action to internal experience, revealing how literature mirrors changing human ideals and worldviews.